UJI AKTIVITAS PERTUMBUHAN RAMBUT KELINCI JANTAN DARI SEDIAAN HAIR TONIC YANG MENGANDUNG EKSTRAK ETANOL DAUN MANGKOKAN (Nothopanax scutellarium L.) - Qurrota Aini (Fakultas MIPA Universitas Tulang Bawang Lampung, 2017)
Preparation stimulating hair growth (hair tonic) is cosmetic preparations used for volumizing hair growth or stimulate hair growth on balding or hair loss. This research aims to formulate hair tonic preparation of extract Nothopanax scutellarium and determine the effect of dosage formulation hair tonic N. scutellarium towards the growth of male rabbit. This research makes five sample formula with active ingredients extract N. scutellarium with concentration 0% (basic hair tonic), 25%, 35%, 45% and positive control (hair tonic preparations containing minoxidil). The treatment is done every day with the volume every time the basting of one mili liter each plot every day for twenty one days. Hair Length measurements performed on days 8 th , 15 th and 22 nd using calipers and the hair weight measurements performed on day 22 by way of shaved hair grows and then weighed. Data were analyzed using ANOVA test. The data length and weight of the negative control hair, formula-A (25%), formula-B (35%), formula-C (45%) and positive control at day 22 in a row is 11.56, 16.19, 14.60, 14.10, 18.58 mm and 387.325, 390.85, 386.9, 387.275, 392.1 mg. Dosage formulations hair tonic of N. scutellarium extract can increase hair growth male rabbits. Keywords : hair grower, extract of Nothopanax scutellarium , anova.